Między asymilacją kulturową a pedagogiką różnicy. Doradca zawodowy w warunkach zróżnicowania kulturowego - Gromkowska-Melosik, Agnieszka (Wydawnictwo Naukowe UAM, 2016)
The article attempts to analyze the problems of vocational counseling in a multicultural society. This problem applies in particular to the countries and societies with a traditionally diverse ethnic strucure, such as, for example, the United States, Canada or Australia. It is expected that in the near future – because of the influx of immigrants from the Third World to areas hitherto culturally homogeneous – this problem can become global. In this context, it is believed that the contextualization of the career of each person in its own cultural conditions of life and cultural identity is necessary. Logically, education of “multicultural counselors” should include: increasing intercultural awareness, extending the scope of knowledge concerning other cultures and the development of a “culturally sensitive competence”.
Between Cultural Assimilation and Pedagogy of Difference. Vocational Guidance Counselor in Cultural Diversity
Keywords: career counseling; multicultural society; career; intercultural awareness